Allgemeine Behandlungsgrundsätze, Versorgungskoordination und Patientenschulung beim Fibromyalgiesyndrom - Petzke, Frank; Schiltenwolf, Marcus (Der Schmerz, 2017)
BackgroundThe regular update of the guidelines on fibromyalgia syndrome, AWMF number 145/004, was scheduled for April 2017.MethodsThe guidelines were developed by 13 scientific societies and 2 patient self-help organizations coordinated by the German Pain Society. Working groups (n =8) with a total of 42 members were formed balanced with respect to gender, medical expertise, position in the medical or scientific hierarchy and potential conflicts of interest. A search of the literature for systematic reviews on randomized, controlled trials on patient education and shared decision-making from December 2010 to May 2016 was performed in the Cochrane library, MEDLINE, PsycINFO and Scopus databases. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine version 2009. The strength of recommendations was achieved by multiple step formalized procedures to reach a consensus. Efficacy, risks, patient preferences, clinical and practical applicability of available therapies were weighed up against each other. The guidelines were reviewed and approved by the board of directors of the societies engaged in the development of the guidelines.Results and conclusionThe diagnosis of fibromyalgia syndrome should be explicitly communicated to the affected individual. Shared decision-making with the patient on the therapeutic options based on individual preferences of the patient, comorbidities and the success of previous treatment is recommended. A step-wise treatment approach depending on the severity of fibromyalgia syndrome and the response to therapeutic measures is recommended.